Future of the German Economic Model - Überblick (Wirtschaftsdienst)
Abstract Thirty years after German reunification — and under distress due to the acute coronavirus crisis — the seventh New Paradigm Workshop of the Forum New Economy took place in Berlin on 28–30 September. Renowned German and international experts discussed the “Future of the German Economic Model”. How well is Germany prepared for the coming challenges? This forum features a selection of articles funded by the Forum New Economy and presented at its workshop, including studies on the development of inequality in Germany, new industrial policy, the relevance of fiscal rules and the pitfalls of the German export model. The forum also includes a translation of the keynote by Thomas Piketty.